The Construction of Plant Expression Vector harbouring Carica Papaya L. WRKY Gene in Escherichia coli - Abu Bakar, Fauziah; Paramalingam, Pavitra; Hasan, Kamariah (Universiti Putra Malaysia Press, 2020)
Carica papaya is a well-liked and economically important fruit with outstanding nutritional and medicinal values. Its susceptibility to abiotic stress which affects the growth and harvest, causes significant yield loss to farmers. In recent years, significant progress has been made to understand the genes that play critical roles in abiotic stress response, especially some transcription factor (TF) encoding genes. Among all TFs, WRKY TF gene family is one of the best-studied TFs involved in various stress responses. To date, only limited information on functionally characterised WRKY TFs is available for C. papaya. The aim of this study was to produce a recombinant construct harbouring WRKY gene in pGEM®-T Easy cloning vector. The presence of a DNA band of the expected size of 465 bp on agarose gel electrophoresis indicated that WRKY gene was successfully amplified from all treated samples. DNA sequencing analysis] revealed that the amplified sequence isolated from the treated samples were closely related to Carica papaya species with 97% similarity. Following transformation, 4 out of 5 colonies that were randomly selected showed the WRKY gene had been successfully inserted into pGEM®-T Easy vector and transformed into E. coli. In future, the WRKY gene from pGEMT-WRKY recombinant construct will be cloned into the plant expression vector pCAMBIA 1304 prior to transformation in the plant. The success of demonstrating the WRKY gene towards the response in abiotic stress will enable us to produce stress tolerant transgenic crops under unfavourable conditions via genetic engineering for sustained growth.